2017
DOI: 10.1016/j.ebiom.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Is Ep-CAM Expression a Diagnostic and Prognostic Biomarker for Colorectal Cancer? A Systematic Meta-Analysis

Abstract: BackgroundCancer stem cell (CSC) epithelial cell adhesion molecule (Ep-CAM) is frequently expressed in colorectal cancer (CRC). However, the clinical significance of Ep-CAM expression in CRC is not clear. This study evaluated whether Ep-CAM provided valuable insight as a molecular biomarker for CRC diagnosis and prognosis and the potential of Ep-CAM as a novel therapeutic target in CRC.MethodsPublications were selected online using electronic databases. The pooled odds ratios (ORs) or hazard ratios (HRs) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
(108 reference statements)
0
39
0
1
Order By: Relevance
“…Numerous studies have shown the molecular mechanisms linked to CRC [6][7][8][9]. Tumor hypoxia is a pathological hallmark that may be correlated with metabolism, the activation of cell signaling, angiogenesis, differentiation, necrosis or cell apoptosis, tumor development and aggressiveness, etc [10][11][12].. Additionally, tumor hypoxia can have an adverse impact on the prognosis of some cancers (i.e., invasive breast cancer or cervical cancer) and the efficacy of chemo-and radiotherapy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the molecular mechanisms linked to CRC [6][7][8][9]. Tumor hypoxia is a pathological hallmark that may be correlated with metabolism, the activation of cell signaling, angiogenesis, differentiation, necrosis or cell apoptosis, tumor development and aggressiveness, etc [10][11][12].. Additionally, tumor hypoxia can have an adverse impact on the prognosis of some cancers (i.e., invasive breast cancer or cervical cancer) and the efficacy of chemo-and radiotherapy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The pooled hazard ratio (HR) and the 95% CI were also calculated to analyze the clinical outcome of MLH1 promoter methylation in GC patients where possible. Heterogeneity of this meta-analysis was detected using the Cochran’s Q statistic [22, 23]. A random-effects model was used for the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the pooled ORs and the corresponding (95% CIs) were also calculated for estimating the correlation between RASSF1A promoter methylation and ovarian cancer in cancer versus LMP tumors. Heterogeneity across the studies was detected based on the Cochran’s Q and I 2 tests [23, 24]. An I 2 value of more than 50% and a p value of <0.1 were considered significant heterogeneity; the random-effects model was used; otherwise, a fixed-effects model was selected in this meta-analysis, suggesting no substantial evidence of heterogeneity [25, 26].…”
Section: Methodsmentioning
confidence: 99%